2008
DOI: 10.1089/hum.2006.196
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Againstneu-Positive Carcinomas Elicited by Electroporation of Plasmids Encoding Decreasing Fragments of Rat Neu Extracellular Domain

Abstract: We have shown that electroporation of plasmid carrying extracellular and transmembrane domains (EC-TM plasmid) encoded by the rat neu oncogene triggers a protective immune response toward rat p185(neu)-positive tumors in both wild-type BALB/c mice and cancer-prone rat neu-transgenic BALB-neuT mice. To identify the critical fragments that confer this protective immunity, mice were electroporated with plasmids encoding the TM domain associated with decreasing fragments of the EC domain and the antitumor protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Collaboration of the humoral and the cellular immune responses in rejection of rErbb2 tumors in transgenic mice has been documented (42). In addition, our previous studies in BALB-neuT mice receiving the adoptive transfer of Abs and T cells have shown the importance of both humoral and cellular reactivity in hampering the progression of mammary cancer (22,24). In BALB-neuT mice receiving an Erbb2 vaccine alone, the role of CD8 + T cells in protecting against rErbb2 tumors is negligible (13,17,28).…”
Section: Discussionmentioning
confidence: 98%
“…Collaboration of the humoral and the cellular immune responses in rejection of rErbb2 tumors in transgenic mice has been documented (42). In addition, our previous studies in BALB-neuT mice receiving the adoptive transfer of Abs and T cells have shown the importance of both humoral and cellular reactivity in hampering the progression of mammary cancer (22,24). In BALB-neuT mice receiving an Erbb2 vaccine alone, the role of CD8 + T cells in protecting against rErbb2 tumors is negligible (13,17,28).…”
Section: Discussionmentioning
confidence: 98%
“…Our results propose that N-terminally fusion of HSP70 to Her2/neu masked or decreased the effect of the signal sequence. Moreover, it has been demonstrated that 70 N-terminal residues of Her2/neu play an important role in effective protection against Her2-expressing tumors (Rolla et al 2008). Therefore, it is also likely that the effect of Nterminal residues of Her2/neu is affected by fusion of HSP70.…”
Section: Discussionmentioning
confidence: 99%
“…Our starting point was the observation that RRT ErbB-2 plasmid elicits a similar or even better response than the one encoding the full length rat ErbB-2 11 . Then, we produced seven plasmids encoding the transmembrane domain associated with decreasing fragments of the extracellular domain 41 . When these plasmids were electroporated in wild-type BALB/c mice, the intensity of the response and protection against a challenge of rat ErbB-2 + murine cells decreased with the shortening of the ErbB-2 fragment encoded.…”
Section: The Sequence Coding For the Antigenmentioning
confidence: 99%